Shareholders and wage determination - Marko Ogorevc; Sonja Slander (European Regional Science Association (ERSA), 2010)
Multinational firms transfer to their foreign affiliates superior technology, leading to higher productivity of their workers and therefore to higher wages, or so the often cited rent-sharing theory of multinational firms explains. But studies have shown that oftentimes, this results not from foreign ownership per se, but from other characteristics, which are positively related to wages and are more prevalent in foreign than in domestically owned firms (for example size, capital intensity, focus on high wage industries, ...). Furthermore, recent research argues that large shareholders (foreign or domestic) differ from each other, and that changes in a firm's policy are greater in the presence of specific groups of active blockholders (Bertrand and Mullainathan (2003), Cronqvist and Fahlenbrach (2007)). The aim of our paper is to disentangle the relationship between ownership and wages for the population of Slovenian joint stock companies, while accounting for "spatial" dependencies in wage determination. We have managed to augment the concept of space which in this paper is not considered in a geographical context, but as a set of ownership relations between firms. We apply methods of spatial econometrics - the spatial error model, while introducing the creation of "shareholder" spatial connectivity matrix.
Keywords: C21; C23; F21; J31; 330; Spatial econometrics; ownership; wage differentials; wage spillovers